A note on harbour seal (Phoca vitulina) distribution and abundance in France and Belgium - Hassani, Sami; Dupuis, Laëtitia; Elder, Jean François; Caillot, Emmanuel; Gautier, Gerard; Hemon, Audrey; Lair, Jean Michel; Haelters, Jan (NAMMCO Scientific Publications, 2010)
The most southern European colonies of harbour seals (Phoca vitulina) are located in France, in three areas: Baie du Mont Saint Michel, Baie des Veys and Baie de Somme. The largest colony is situated at the Baie de Somme, with a maximum of 186 individuals recorded on one occasion in the summer of 2008. All colonies are regularly monitored by different organisations. Different monitoring methods are used, including land-based, air-based and ship-based survey techniques. The basic results of the monitoring indicate a regular increase in the population size since 1990, with the total count of hauled out harbour seals for the three colonies increasing from 24 in 1990 to 295 in 2008. During the last years, an increasing number of pregnant females, pups and postweaned seals have been observed. The recorded number of pups in 2008 was 53. Along the Belgian coast, no harbour seal colonies exist anymore, although individual animals and small groups are regularly observed at different locations. The high recreational use of Belgian beachesmay prevent the establishment of colonies or regularly used haulout sites.